Group-specific effect of interannual water level fluctuation on consumers trophic niche area - Veselý, Lukáš; Ruokonen, Timo J.; Ercoli, Fabio; Bláha, Martin; Buřič, Miloš; Balzani, Paride (Springer Nature, 2026)
The trophic niche area defines the consumer’s ability to utilize a range of food sources and their role in community. However, the trophic niche area might be influenced by a variety of biotic and abiotic factors. For instance, water level fluctuation might also affect the trophic niche area of all consumers inhabiting a given aquatic ecosystem. Thus, in this study we investigated the effect of water level fluctuation on the isotopic niche area of multiple consumers (macroinvertebrates and fish) belonging to different trophic guilds (i.e., predator, omnivore, and detritivore) over three years. The results showed that water level fluctuation strongly affects the isotopic niche area of all consumers. Nevertheless, the magnitude and direction were group specific. While predatory fish increased the isotopic niche area when the water level dropped, omnivorous fish experienced a decrease; these two trends continued even after the water level drop. In crayfish, the isotopic niche area was considerably larger during the year with water level drop. However, decreasing water levels resulted in a corresponding decrease in isotopic niche area in detritivores and predatory macrozoobenthos. Our study demonstrated the importance of water fluctuations on the isotopic niche area across different types of consumers.
Keywords: stable isotopes; carbon; nitrogen; fish; crayfish; macrozoobenthos